“Reading Together” Two Historical Novels in Afan Oromo and Amharic: Linguistic Diversity in the Ethiopian Literary Field - Roba, Ayele Kebede (Research in African literatures, 2025)
Ethiopian monolingual language policies have had a negative impact on literary practices and studies; however, it is an area highly neglected in Ethiopian literary studies. The present article contributes to this gap through a multilingual comparative approach that adopts a method of “reading together” of the novels in two widely spoken languages: Amharic and Afan Oromo. Reading together two historical novels, Yeburqa Zimita [ Burqa’s Silence ] and Yoomi Laataa? [ When Shall It Be? ], from the perspective of the novels’ engagement with multilingualism enables an often-neglected comparative study between the literatures in different Ethiopian languages. The article examines how and why the novels are open to multilingualism and how their positionality in different literary traditions conditions their representation of multilingualism. It also demonstrates how a reading method that takes multilingualism in the novel as an analytical category overcomes disjunctive and conflicted Ethiopian literary practices and studies.